Characterizing patterns of small pneumoconiotic opacities on chest radiographs of New Mexico coal miners. Issue 4 (21st April 2022) - Rehman, Mueez; Sood, Akshay; Pollard, Charles; Johnson, Diane; Vlahovich, Kevin; Myers, Orrin; Shore, Xin; Cook, Linda; Assad, Nour
Abstract: Small pneumoconiotic opacities in coal miners are usually described as rounded, regular, and upper zone predominant. We aim to characterize chest radiographic patterns in New Mexico coal miners in comparison with other miners. Of the 330 chest radiographs reviewed, small pneumoconiotic opacities in New Mexico miners were almost always irregularly shaped, and lower lung zone predominant, consistent with diffuse dust-related pulmonary fibrosis. There was no significant difference in patterns of opacities between miners with exposure to coal mine dust exclusively, mixed coal and noncoal mine dust, and no coal dust. Our findings indicate that New Mexico coal miners demonstrate a different pattern of small pneumoconiotic opacities than the classic nodular pneumoconiosis described in the literature, predominantly from Appalachian miners. This may indicate differences in racial/ethnic characteristics or in the silica/silicate content of dust between the Appalachian and Mountain West regions.